Peran Kelompok Dukungan Bagi Keberhasilan Ibu Bekerja Memberikan ASI Eksklusif: Dukungan Kelompok Menyusui bagi Ibu Bekerja Berhasil Memberikan ASI Eksklusif di Kota Manado - Rakhmawati Agustina (Universitas Airlangga, 2022)
Background: The coverage rate of exclusive breastfeeding in North Sulawesi Province is 39.7% in 2021. Return of women to the workplace is one of the factors contributing to the failure of exclusive. Breastfeeding support groups has an impact on their desire to provide exclusive breastfeeding. The North Sulawesi Breastfeeding Care Community (KAPAS) is established in Manado in 2016 and consist of more than 200 members. Objectives: investigate the role of support groups for working mothers giving exclusive breastfeeding Methods: A phenomenological design was used in qualitative research. Informant were purposefully chosen. Inclusion criteria are mothers who successfully breastfed exclusively their baby aged six to twenty-four months, full-time jobs in the formal sector, worked and lived in Manado with their baby. Exclusion criteria are mother who have twin babies, pregnant mother, premature, unhealthy, and low birth weight baby. The interview was transcribed and analyzed using the opencode. Results: Following screening to 195 mothers, 5 major informants and 2 supporting informant. In-depth interviews were used to collect the data. The findings revealed that working mothers' desire to exclusively breastfeed as motivation to join KAPAS. When a mother joins KAPAS can be overcome internal and external challenges confidently. Working mothers gained more expertise in managing expressed breast because of the information in the group. Furthermore, mothers have a willingness to discuss their desire giving exclusive breastfeeding to hospital staff. KAPAS give support through emotional, instrumental, and informational support. Conclusions: KAPAS give emotional, instrumental, and informational support so they can successfully give exclusive breastfeeding.